Obstacles to the Quality of Education According to the Credit Hour System at the College of Physical Education and Sports Sciences University of Samarra - Mohammed, Azzam Makki; Abdulmaged, Mustafa Ahmed; Al-Samarrai, Ammar Fares Attia (Jurnal Pendidikan Kepelatihan Olahraga (Pejuang), 2025)
Research Objectives: To construct a questionnaire on the obstacles to the quality of education according to the credit hour system from the faculty members' perspective. To identify the obstacles to the quality of education according to the credit hour system. The researchers used the descriptive methodology with a survey method due to its suitability for the nature of the research. The research population and sample were selected from the faculty members of the College of Physical Education and Sports Sciences / University of Samarra, numbering (33). The researchers employed several statistical tools to reach results that achieve the research objectives. The researchers concluded that obstacles to the quality of education according to the credit hour system exist. The item "(Compulsory courses are proportional to the objectives of the educational process)" was identified as the highest-ranking obstacle. The researchers also put forth several recommendations, including the need for continuous attention to developing and improving the quality of education under the credit hour system.